Litologi Daerah Rawan Banjir Di Desa Batik Nau Dengan Menggunakan Metode Vertical Electric Sounding (VES) - Barasa, Habel; Suhendra, Suhendra; Gustan, Nesti Fazeza; Halauddin, Halauddin (Universitas Andalas, 2025)
This study was conducted to determine the type of rock lithology in Batik Nau village to see its effect on flooding during the rainy season. The study was conducted using the Schlumberger Configuration with the Vertical Electrical Sounding (VES) method at 30 sounding points. VES data collection in this study used the X612-EM MULTI-CHANNEL RESISTIVIMETER. Furthermore, to obtain a 1D log image, Progress 3.0 software was used and then analyzed to be interpreted against the geological map of the research area. The rock porosity value was obtained using the Achi formula using Microsoft Excel software. The results of the interpretation that most of the Batik Nau Village area is dominated by Clay and Napal rocks, both rocks have very low average porosity values ​​so that they are saturated with water. Rock lithology that cannot absorb water perfectly or is in a state of saturation makes this area prone to flooding during the rainy season.